(untitled) (Mwanga wa Lugha, 2022)
A contested site of ‘organized’ chaos, the matatu industry renders itself to analysis due to its nature. The industry, deemed to be for the poor and thus on the peripheries, carries within it intricacies worth appreciation. For a long time, the industry has been marred with chaos, disorder and complete disregard of the rule of law. However, despite this state that forces society to enforce order (uniforms, crackdowns), the matatu industry, for this paper, offers rich fodder for social commentary. This paper, premised on an on-going study, reads the matatu culture as a mirror within which social, political and economic realities are expressed within the mobile text. It is thus an attempt at reading the matatu slogans as the practices of everyday aimed at circulating certain ideologies. The paper’s discussion is grounded on the discourse theory developed by the French philosopher Michel Foucault (1926-1984) and on selected tenets of The Practice of Everyday Life as espoused by Michel de Certeau (1925-1986). Specifically, the paper seeks to examine the extent to which matatu slogans and mottos are a reflection of urban culture, analyse the social relevance and significance of matatu slogans and mottos, and present a syntactical analysis of the matatu slogans and mottos. Adopting a qualitative approach, it reads a mobile text with the intention of inspecting the relationship between matatu slogans and urban cultures in Eldoret . The author relies on ethnographic and social survey methodology to explore the writing of short catchy texts that take the form of ‘creolized proverbs’, not necessarily traceable to any particular oral tradition in Kenya but which seem to be a summary of local experience and distillation of local anxieties and aspirations. The study collected at least 20 ‘matatu proverbs’. An observation checklist and camera were used to collect data. The information collected on the inscriptions was organized in categories based on the most common emerging themes. From the 20 randomly collected slogans, it emerged that the most common theme is on morality and social education. This is followed by religious messages. Overall, matatu slogans are syntactically arranged to emphasize meaning, provoke thinking and make the messages punchy and memorable. Matatu slogans hold significant value to society. They admonish people about hard work and moral uprightness. They also criticise insincerity and dishonesty. Matatu slogans also reflect the inherent urban culture. This culture is chaotic and forces individuals to survive by any means. It is a money-driven culture. While many would do anything to survive in this culture, majority still hold on to their religious and moral commitments.